1985
DOI: 10.1128/mcb.5.10.2669
|View full text |Cite
|
Sign up to set email alerts
|

Differential regulation of trypsinogen mRNA translation: full-length mRNA sequences encoding two oppositely charged trypsinogen isoenzymes in the dog pancreas.

Abstract: In the absence of changes in functional mRNA levels, stimulation of the pancreas with caerulein, a peptide analog of cholecystokinin, has been previously shown to increase the synthesis of anionic but not cationic trypsinogen. To look for structure-function correlations, a high-yield, full-length cDNA library has been constructed from canine pancreatic poly(A)+ mRNA. Full-length clones coding for the two major trypsinogen isoenzyme forms have been identified by colony hybridization and verified by in vitro tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
42
0
1

Year Published

1987
1987
2013
2013

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 62 publications
(43 citation statements)
references
References 9 publications
0
42
0
1
Order By: Relevance
“…This is illustrated in Fig. 4a together with the potential hybridization of the 5'-noncoding region of dog anionic trypsinogen as demonstrated by Pinsky et al [ 5 ] . Kern et al [29] have proposed that hormonal stimulation opens up the stem structure of 18s ribosomal RNA to allow binding of a complementary region of rat anionic trypsinogen while the complementary region of cationic trypsinogen has a potential hybridization site to a region flanking the stem structure.…”
Section: S'-noncoding and 3'-noncoding Regionsmentioning
confidence: 61%
See 1 more Smart Citation
“…This is illustrated in Fig. 4a together with the potential hybridization of the 5'-noncoding region of dog anionic trypsinogen as demonstrated by Pinsky et al [ 5 ] . Kern et al [29] have proposed that hormonal stimulation opens up the stem structure of 18s ribosomal RNA to allow binding of a complementary region of rat anionic trypsinogen while the complementary region of cationic trypsinogen has a potential hybridization site to a region flanking the stem structure.…”
Section: S'-noncoding and 3'-noncoding Regionsmentioning
confidence: 61%
“…The RNAs of small ribosomal subunits from all biological sources show extensive nucleotide sequence similarities at their 3' ends [28]. It has been shown that both cationic and anionic trypsinogens contain sequences which are complementary to overlapping regions of eucaryotic 18s ribosomal RNA [5] (Fig. 4a).…”
Section: S'-noncoding and 3'-noncoding Regionsmentioning
confidence: 99%
“…In pulse-chase studies under basal or hormone-stimulated conditions, nascent proteins, synthesized in pancreatic lobules during a pulse period of 10 Despite detailed knowledge of the mRNA sequences that encode pancreatic digestive enzymes in mouse (19), rat (18,35), and dog (9,20) Sequences are from the following references: anionic trypsinogen mRNA from the dog (9) and rat (18); amylase mRNA from the dog (K. S. LaForge and G.A.S., unpublished data), mouse (19), and rat (35). proteins, possibly altered by second messenger-activated pathways, may be responsible for differentially altering initiation of translation of individual mRNAs.…”
Section: Methodsmentioning
confidence: 99%
“…Recently, translational control has been demonstrated for insulin biosynthesis in response to changes in glucose concentrations in the blood circulation in the rat (4), for a 70-kDa protein during the response to heat shock in Drosophila (5), and for a group of =20 proteins during the early mitotic response in 3T3 cells (6). In the exocrine pancreas, we have reported that the synthesis of anionic but not cationic trypsinogen is regulated at the level of mRNA translation during caerulein stimulation (7)(8)(9). We now report that the divergent changes in synthesis of anionic trypsinogen and amylase during a 24-hr period of caerulein stimulation are regulated through mechanisms of translational control.…”
mentioning
confidence: 96%
“…In mammalian species, the different isozymes are classified, depending on their isoelectric point, as cationic (pI > 7.0) or anionic (pI < 7.0). Charge distribution along the sequence appears to be very similar within each cationic and anionic trypsin group (Pinsky et al, 1985), while human trypsin 1 shows intermediate features. Peculiarities of its charge distribution will thus be analyzed in the three-dimensional space.…”
Section: Introductionmentioning
confidence: 91%